Religious Affiliation, Daily Spirituals, and Private Religious Factors Promote Marital Commitment Among Married Couples: Does Religiosity Help People Amid the COVID-19 Crisis? - Aman, Jaffar; Abbas, Jaffar; Lela, Umi; Shi, Guoqing (Frontiers in Psychology, 2021)
Religious studies are a vital branch of social science that seeks to explain human society's beliefs and deals with individuals' practices and beliefs. This distinctive study focuses on such influential aspects of a healthy life, which could play a vital role in individuals’ marital quality and matrimonial commitment. The study principally focused on inspecting the role of religiosity in healthy marital commitment among individuals. It is a distinctive and central value in regulating a healthy social life. This research designed a conceptual model for assessing marital commitment, and the study model comprised two primary variables. The study received the data sets through a survey questionnaire based on the participants from five private and public sectors. The research study conducted an empirical analysis to test the proposed conceptual framework. The findings exhibited that the value of the R² model was 0.484, meaning that the level of religiosity had a substantial impression on healthy and lasting marital commitment. According to the final outline of the model factors associated with building religious support factors (β = 0.491), the marital commitment had a better and healthier impact. The goodness-of-fit of the conceptual model’s measurement showed a value of 0.51, which indicated that the theoretical model had sufficient consistency and rationality and accurately fitted the data. Such an advanced statistical model is missing from the previous literature. The study results provide helpful insight to elucidate marital commitment's social dynamics. The findings designate that religious practices strengthen and promote nuptial commitment. The study is novel in the context of religiosity impact on martial commitment with a cultural background of Pakistan. The study's generalizability does not apply to the entire population or other regions. Future studies can investigate other religious variables to explore further research findings. The findings are helpful for decision-makers and policymakers to concentrate on the marital issues and challenges confronted by couples worldwide.